Containing Iran Strategies for Addressing the Iranian Nuclear Challenge - Reardon, Robert J. (RAND Corporation, 2012)
Iran's nuclear program is one of this century's principal foreign policy challenges. Despite U.S., Israeli, and allied efforts, Iran has an extensive enrichment program and likely has the technical capacity to produce at least one nuclear bomb if it so chose. This study assesses U.S. policy options, identifies a way forward, and considers how the United States might best mitigate the negative international effects of a nuclear-armed Iran.